Appropriate processing technology for rubberwood in Ghana - Addae-Mensah A G; Ayarkwa J; Eastin I L (Wood News, 1993)
The bulk of plantations of Rubberwood(Hevea brasiliensis) in Ghana is, in comparison to some other West African countries pretty small. Planted areas in the Ivory Coast is known to be about 54000 ha whereas Nigeria and the Cameroons each lie in the range of about 182000 ha and above. Liberia has over 192000 ha with Ghana having only 11000 ha. Whereas it is especially acknowledged that rubberwood is endowed with the main objective of producing latex in the manufacture of rubber, however new exploitation orientation in view of its transformation into sawn timber apparently offer interesting and very economic possibilities. This paper tries to discuss some characteristics of Rubberwood in Ghana and the methods of a suitable transformation mechanism.
Keywords: Ghana; Rubber wood processing; Sawmilling